A comparative study to assess the effect of balance training with and without taping on balance in stroke patients - Amina Farid Khan; Fouzia Batool; Saima Gul; Roshneck Hameed; Esha Khan; Saher Fatmi (Journal of the Pakistan Medical Association, 2026)
Objective: To evaluate the effect of balance training with and without taping on balance in patients with sub-acute or chronic stroke. Method: The parallel-arm, prospective study was conducted at the Pakistan Institute of Rehabilitation Sciences, Islamabad, Pakistan, from May to August 2023, and comprised stroke patients of either gender aged >35 years who had a stroke onset history of at least three months. The patients were randomised into experimental group A, exposed to balance training with taping, and control group B, exposed to balance training without taping. The intervention was administered for 30 minutes per day, three sessions per week for four consecutive weeks. The Berg Balance Scale was used at baseline and post-intervention. Data was analysed using SPSS 26. Results: Of the 36 participants with mean age 52.19 ±11.38 years, 18(50%) were in group A; 11(61.1%) females and 7(38.39%) males. The remaining 18(50%) patients were in group B; 10(55.6%) females and 8(44.4%) males. Both the groups showed significant improvement in terms of balance recovery compared to baseline values (p<0.05), but group A patients showed significantly higher results than their group B counterparts (p<0.05). Conclusion: Balance training with taping was found to be more effective for the improvement of balance than balance training without taping in sub-acute to chronic stroke patients. Key Words: Balance training, Taping, Stroke patients, Comparative study, Balance improvement.